Tailor‐made PAT platform for safe syngas fermentations in batch, fed‐batch and chemostat mode with Rhodospirillum rubrum - Stephanie Karmann; Stéphanie Follonier; Daniel Egger; Dirk Hebel; Sven Panke; Manfred Zinn (Microbial Biotechnology, 2017)
Summary Recently, syngas has gained significant interest as renewable and sustainable feedstock, in particular for the biotechnological production of poly([R]‐3‐hydroxybutyrate) (PHB). PHB is a biodegradable, biocompatible polyester produced by some bacteria growing on the principal component of syngas, CO. However, working with syngas is challenging because of the CO toxicity and the explosion danger of H2, another main component of syngas. In addition, the bioprocess control needs specific monitoring tools and analytical methods that differ from standard fermentations. Here, we present a syngas fermentation platform with a focus on safety installations and process analytical technology (PAT) that serves as a basis to assess the physiology of the PHB‐producing bacterium Rhodospirillum rubrum. The platform includes (i) off‐gas analysis with an online quadrupole mass spectrometer to measure CO consumption and production rates of H2 and CO2, (ii) an at‐line flow cytometer to determine the total cell count and the intracellular PHB content and (iii) different online sensors, notably a redox sensor that is important to confirm that the culture conditions are suitable for the CO metabolization of R. rubrum. Furthermore, we present as first applications of the platform a fed‐batch and a chemostat process with R. rubrum for PHB production from syngas.